2018
DOI: 10.1155/2018/7315797
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency as It Relates to Oral Immunity and Chronic Periodontitis

Abstract: The biologically active form of vitamin D, 1,25 dihydroxyvitamin D (1,25(OH)2D) and its receptor, the vitamin D receptor (VDR), play roles in maintaining oral immunity and the integrity of the periodontium. Results of observational cross-sectional clinical studies investigating the association between vitamin D serum level and the incidence and severity of chronic periodontitis indicate that, perhaps owing to the immunomodulatory, anti-inflammatory, and antibacterial properties of 1,25(OH)2 D/VDR signalling, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 61 publications
1
65
0
5
Order By: Relevance
“…While oral supplementation of vitamin D can lead to vitamin D sufficiency in vitamin D‐deficient individuals, including those with chronic periodontitis, the natural feedback mechanism based on the induction of the vitamin D 24‐hydroxylase enzyme guarantees that high concentrations of 1,25(OH) 2 D 3 will not occur in the gingival epithelium. Because of this, hypervitaminosis D and other side effects of high levels of supplementation are rare .…”
Section: Discussionmentioning
confidence: 99%
“…While oral supplementation of vitamin D can lead to vitamin D sufficiency in vitamin D‐deficient individuals, including those with chronic periodontitis, the natural feedback mechanism based on the induction of the vitamin D 24‐hydroxylase enzyme guarantees that high concentrations of 1,25(OH) 2 D 3 will not occur in the gingival epithelium. Because of this, hypervitaminosis D and other side effects of high levels of supplementation are rare .…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of serum 25(OH)vitD levels within normal range modulates a patient's respond to periodontal treatment 16,31 . Although vitamin D supplementation is associated with decreasing severity of chronic periodontitis, further investigation is required to establish the vitamin's deficiency as an indisputable risk factor 32 . Insufficient calcium intake has been correlated with periodontal disease mainly through its impact on bone metabolism 33 .…”
Section: ) Smokingmentioning
confidence: 99%
“…Periodontitis is associated with imbalanced immune homeostasis in the oral mucosa, with increased bacterial growth and multiplication in the dental plaque. Most of these microorganisms induce an increase in pH and a reduction in the local redox potential, with the upregulation of inflammatory mediators [6] leading to the onset and progression of the disease [7,8]. Immune response in PD is imbalanced, with 70% of B-cell subset dominance and only 30% of the macrophage, neutrophil, and T-cell subset [9,10], in association with an increased level of inflammatory cytokines like interleukin (IL)-1, tumor necrosis factor (TNF)-α, interferon (IFN)-γ, IL-17, and IL-6 [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…The circulating metabolite of vitamin D, 25-hydroxy vitamin D 3 (25(OH)D 3 ), binds the vitamin D receptor [18], playing an important role in oral health maintenance through antibacterial, antiviral, and anti-inflammatory activity. The active form of vitamin D (1,25(OH)2D 3 ) leads to the regulation of both innate and adaptive immunity, modulating inflammatory cytokine production and blocking antigen-presenting dendritic cell maturation with a decrease of antigen-specific T-cell activation and proliferation, associated with regulatory T cell (Treg) activity promotion [7,18,19]. Liu et al [20] have demonstrated the involvement of 25(OH)D 3 and IL-1β in patients with generalized aggressive periodontitis, both in local and systemic evaluation.…”
Section: Introductionmentioning
confidence: 99%